(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article explores the multifaceted landscape of modern teaching methodologies, delving into key components shaping contemporary education. From technology integration and personalized learning to inclusivity and community engagement, the article outlines transformative approaches that redefine the teacher-student dynamic and prepare learners for the demands of the 21st century.